The positive summarized effect of the creative life-orientation phenomenon - Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна (Canada : Accent graphics communications, 2017)
The paper is devoted to summing up the results of studying the creative life-orientation as a personal phenomenon, which has a multi-level system-forming structure consisting of a hierarchy of interdependent and interacting components. The author’s program (for the creative life-orientation activation in the process of subjects’ interaction during their educational and professional activity) is developed and the innovative technology of its manifestation is tested in the framework of the teaching «Self-organizing Psychological System», by the example of linguistic education. A positive relationship between the person’s creative life-orientation, spirituality and psychosomatics has been established. The developmental-correcting role of the creative life-orientation has been empirically confirmed, as well as the anti-stress function in the process of personality’s self-establishment and self-development has been revealed. Cтатья посвящена подведению итогов по исследованию жизнесозидающей креативности как личностного феномена, которая имеет многоуровневую системобразующую структуру, состоящую из иерархии взаимозависимых и взаимовлияющих компонент. Разработана авторская инновационная программа ее активизации при взаимодействии субъектов учебно-профессиональной деятельности и апробирована технология ее проявления в рамках обучающей «самоорганизующейся психологической системы» (на примере лингвообучения). Установлена позитивная взаимосвязь между жизнесозидающей креативностью, духовностью и психосоматикой человека. Эмпирически подтверждена развивающе-корректирующая роль, а также выявлена антистрессовая функция жизнесозидающей креативности в процессе самостановления и саморазвития личности.
Keywords: creative life-orientation; spirituality; psychosomatics; Self-organizing Psychological System; жизнесозидающая креативность; духовность; психосоматика; Самоорганизующаяся Психологическая Система